2011
DOI: 10.1111/j.1365-313x.2011.04727.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase III in pomegranate seeds (Punica granatum Linn.): a high‐capacity calcium‐binding protein in amyloplasts

Abstract: ). † These authors contributed equally to this work. SUMMARYChitinases are a class of ubiquitous proteins that are widely distributed in plants. Defense is the major natural role for chitinases, primarily against fungal pathogens. Little is known regarding their non-defensive roles in seeds. In this study, a new class III chitinase from pomegranate seeds (pomegranate seed chitinase, PSC) was isolated and purified to homogeneity. The native state of PSC is a monomer with a molecular weight of approximately 30 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…8,16 This result is in good agreement with its isoelectric point (4.6). Furthermore, MALDI-TOF-MS and X-ray diffraction (XRD) analyses showed that these acidic amino acid residues in PSC are responsible for the binding of 10 calcium ions 14 with a similar way to reported Ca-storage proteins.…”
Section: Prediction Of Three Dimensional Structure Of Chitinase III Isupporting
confidence: 53%
See 2 more Smart Citations
“…8,16 This result is in good agreement with its isoelectric point (4.6). Furthermore, MALDI-TOF-MS and X-ray diffraction (XRD) analyses showed that these acidic amino acid residues in PSC are responsible for the binding of 10 calcium ions 14 with a similar way to reported Ca-storage proteins.…”
Section: Prediction Of Three Dimensional Structure Of Chitinase III Isupporting
confidence: 53%
“…cells of pomegranate seeds. 14 On the other hand, PSC binds calcium ions with high capacity and low affinity, suggesting that PSC could be a calcium storage protein in pomegranate seeds. If this were the case, we would expect that the amyloplasts of the embryonic cells are rich in calcium ions.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation
“…3(a)), suggesting that the PSC is active class III chitinase. In fact, we demonstrated the chitin hydrolytic activity of the PSC in our previous report, 11) the k cat /K m value of PSC is much lower than that of another active class III chitinase hevamine. 24,25) Activity center and conserved non-proline cis-peptide The active site (Asp125 and Glu127) of PSC is well superimposable with that of hevamine, whereas the glutamate is substituted by glutamine in concanavalin B and both of the two residues are absent in the sequence of chi-lectin.…”
Section: Resultsmentioning
confidence: 53%
“…To date, different types of chitinases have been purified and characterized from different plants like sugar beet (El Sayed et al, 2000), soya bean (Gijzen et al, 2001), pineapple (Taira et al, 2005), pomegranate (Yang et al, 2011), and persimmon (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%